IMPACT OF CORPORATE SOCIAL RESPONSIBILITY AND GREEN INNOVATION ON ENVIRONMENTAL PERFORMANCE IN COMMERCIAL BANKS OPERATING IN SINDH - Shahzadi Khand; Muneer Ahmed Shah; Nazar Hussain; Arooj Fatima; Shumaila (International Journal of Contemporary Issues in Social Sciences, 2023)
This research attempts to observe the impact of corporate social responsibility and green innovation on environmental performance by employing primary data collected through a survey questionnaire from commercial banks working in Sindh, Pakistan. The convenience sampling technique was applied for data collection. In total, 84 questionnaires were distributed among the employees of commercial banks; 78 questionnaires were filled out properly, and the remaining questionnaires were discarded. After data collection, it was analyzed in Smart PLS 4. The findings of the study show the positive and significant effect of CSR and GI on environmental performance. This suggests that greater attention must be paid by banks to leveraging CSR and GI to enhance their ability to improve environmental performance. Moreover, this research adds to the theory of legitimacy by examining how banking institutions fund and carry out corporate social responsibility inventiveness that, as a social force and as required by law, businesses should engage in order to promote environmental sustainability and social acceptance. Furthermore, green initiatives help banking institutions improve their environmental performance, such as green technology, online banking, and customer service.